The The Influence of Blended Learning Methods Through the Use of Google Classroom Media on Student Achievement at Islamic Education - Rizky Septi Maulana Habibie; Afif Kholisun Nashoih (SCHOOLAR: Social and Literature Study in Education, 2022)
The purpose of this study is to prove significantly the influence of bleanded learning method through the use of google classroom media on student achievement in PAI subjects at SMP Plus Darussalam Jember.. This research is quantitative research. The study sample consisted of 98 respondents but the researchers only took a sample of 78 students. . influence of bleanded learning method through the use of google classroom media on student achievement in PAI subjects at SMP Plus DarussalamJember. The results showed that the use of bleandead learning method through google classroom positively and significantly affects student learning outcomes in PAI subjects with this can be seen from the hypothetical test results of 0.474 > 0.05 so it can be said that there is an influence of bleanded learning method through the use of google classroom media on student achievement in PAI subjects in SMP Plus Darussalam Jember.